Factores de incidencia en el desarrollo de mecanismos resilientes en jóvenes mujeres y hombres, entre 25 y 30 años refugiados o solicitantes de refugio atendidos por HIAS en la ciudad de Quito en el periodo 2016 - 2017 - Jaramillo Viteri, Jorge Andrés (2018)
This document evidences the results of the research on the factors that influence the development of resilient mechanisms in refugees or asylum seekers, hosted by the Ecuadorian State and that have been attended by the HIAS organization in the period 2016 - 2017. The methodological development carried out in the research was approached from a qualitative perspective, using content analysis as a method. This allowed to determine, from the discourses raised by the interviewees, those factors that affect the development of resilient mechanisms. Also, it should be considered that the main concepts on which the research was structured are: Mental Health and Resilience. The first of these is the central framework on which the investigative process is carried out, while the second is the basis that determines the central objective of the investigation. Mental Health was worked from the proposal of Martín-Baró (1986), while the concept of Resilience that was used is based on the work of Cyrulnik et al., (2002), who understand this as the development of the potentials of the person who lives adverse moments. The objective of the research was to determine the factors that influence the development of these potentialities for the adaptation of people in situations of forced displacement, so that they can develop resilient mechanisms.